Leaf Extracts of Azadirachta indica and Terminalia arjuna Induce Death of HeLa cells without DNA Degradation - Chowdhury, Miraj Kobad; Ahsan, Nazmul; Akhand, Anwarul Azim (Dhaka University Journal of Pharmaceutical Sciences, 2010)
Cancer is one of the major causes of death all over the world. Different attempts have been taken for the prevention and cure of this devastating disease. Along with various chemically synthesized drugs, extracts from different medicinal plants have been studied to combat cancer. In this study, the effects of leaf extracts from Azadirachta indica and Terminalia arjuna have been investigated on HeLa cells, a well known human cancer cell line. Both of the extracts were found to cause death of HeLa cells dose-dependently. However, the extract of T. arjuna was found more promising than the extract of A. indica in mediating cell death. At a concentration of 50 μg/ml, T. arjuna extract killed 95% cells, whereas the same concentration of A. indica extract killed only 55% cells. In many cases, cell death induced by various chemicals often involves fragmentation of DNA. In this study, the extracts of both plants did not induce any detectable level of HeLa cell DNA fragmentation as demonstrated by agarose gel electrophoresis. This result argued that the cell death might occur before initiation of the process of cellular DNA fragmentation bypassing the apoptotic pathway of cell death. Key words: Cancer; Cell death; Azadirachta indica; Terminalia arjuna. DOI: 10.3329/dujps.v8i1.5339 Dhaka Univ. J. Pharm. Sci. 8(1): 75-79, 2009 (June)